3D Structure and Mechanics of Silk Sponge Scaffolds Is Governed by Larger Pore Sizes - Ferreira, Betina M. P.; Andersson, Niklas; Atterling, Erik; Engqvist, Jonas; Hall, Stephen; Dicko, Cedric (Frontiers in Materials, 2020)
Three-dimensional scaffolds play an essential role in tissue engineering. Although essential, the tunability of the 3D scaffolds mechanical and transport properties remains a challenge. In this work, we present new approaches to advance the field. First, we applied our progressive pH acidification to mimic the natural silk gelation process before ice-templating ( -20 and -80 C); second, we fitted the mechanical properties using a connectivity model; third, we fitted the scaffolds mechanical relaxation to understand the transport properties; and fourth we used micro-CT to correlate the process parameters to the scaffolds’ performances. Our results suggested that the free shrinkage of the scaffolds determined their final properties. We found, however, that the porosity (above 90%) was anisotropic, similarly the tortuosity (between 1 and 1.3). We identified two major pore dimensions, the first one between 10 and 20 µm, and the second between 50 and 130 µm. Mechanically, our model suggested that the bulk modulus captured the elastic contribution and was controlled predominantly by the silk concentration. We tentatively associated the fractional modulus 1 to the collapse of the larger pores structures and was controlled mostly by the process temperature. We assigned the slow relaxation to the transport of fluid in the silk sponge scaffolds; and the fast relaxation with a viscoelastic relaxation. The silk concentration and process temperatures did not influence the latter. Overall, our use of the tomography, mechanical test, and detailed statistical analysis provides inroads into the interplay between process parameters (silk concentration and process temperature) and the multiple responses of the silk sponge scaffolds. The development of a new mechanical fitting for the compression test helped capture simply the different failure modes in the sponge scaffolds as well as correlated those events to relaxation and eventually transport properties.